2009
DOI: 10.1245/s10434-009-0623-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Novel Diagnostic and Therapeutic Tools for Pancreatic Ductal Adenocarcinoma?

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is known for its very poor overall prognosis, making tools for early diagnosis and new therapeutic modalities urgently needed. MicroRNAs (miRNAs), endogenous noncoding RNA molecules of approximately 22 nt, have gained attention as an epigenetic component involved in the development of many cancers, including PDAC. miRNA expression profiles of varying pancreatic tissues have identified a number of differentially expressed miRNAs and seem to be able to differentiate betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…The involvement of miRNAs in various human tumors suggests that they could also have regulatory functions in pancreatic cancer. Several miRNAs have been revealed as 'onco(genic)-miRs' or 'tumor-suppressor miRs' involved in pancreatic tumor development [17,18]. Yet, the molecular mechanisms of miRNAs in pancreatic cancer and their relationship with these regulatory factors are currently poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of miRNAs in various human tumors suggests that they could also have regulatory functions in pancreatic cancer. Several miRNAs have been revealed as 'onco(genic)-miRs' or 'tumor-suppressor miRs' involved in pancreatic tumor development [17,18]. Yet, the molecular mechanisms of miRNAs in pancreatic cancer and their relationship with these regulatory factors are currently poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…And certain cancer histotypes can be classified based on miRNA expression profiles [14][15][16]. In pancreatic cancer, a multitude of misexpressed miRNAs have been reported, such as 'onco(genic)-miRs', miR-21 and miR-155, and 'tumor suppressor miRs', miR-29b and the miR-34 and let-7 families [17,18]. Moreover, it was recently found that miR-96 functions as a tumor-suppressor gene in pancreatic cancer by repressing KRAS expression [19].…”
Section: Introductionmentioning
confidence: 99%
“…5 These endogenous small noncoding RNA molecules of approximately 22 nucleotides display a critical role as epigenetic regulators of gene expression, acting posttranscriptionally through binding to their target messenger RNA (mRNA), resulting in translation inhibition. Microarray technology has revealed differential microRNA expression patterns depending on the tissue and cell type, and even on the developmental stages of a tumor.…”
Section: Introductionmentioning
confidence: 99%
“…With profound understanding of the miRNA target genes and the cellular behaviors influenced by them, miRNA may become exciting targets for cancer therapy (Cho, 2010). Growing evidence suggests that aberrant miRNA expression contributes to the development and progression of PDAC (Bloomston et al, 2007;Szafranska et al, 2007;Mardin & Mees, 2009).…”
Section: Introductionmentioning
confidence: 99%